2016
DOI: 10.1111/cas.13022
|View full text |Cite
|
Sign up to set email alerts
|

Phase I, multicenter, open‐label, dose‐escalation study of sonidegib in Asian patients with advanced solid tumors

Abstract: Sonidegib is a selective inhibitor of Smoothened receptor, which is a key regulator of the Hedgehog signaling pathway. The purpose of this study was to determine the maximum tolerated dose based on dose‐limiting toxicity (DLT) and the recommended dose (RD) of sonidegib in Asian patients with advanced solid tumors. This was an open‐label, single‐arm, multicenter, two‐group, parallel, dose‐escalation, phase I study undertaken in Asian patients; group 1 included patients from Japan and group 2 included patients f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…CK elevation was the most common grade 3/4 event, occurring in 6% of patients taking the 200 mg dose; women show a lower risk of CK abnormality than men 52. Furthermore, CK elevations were observed at low doses in Japanese patients, which resulted in their lower MTD of sonidegib 48,49. Serious adverse events, including rhabdomyolysis and very high CK, were very rarely associated with sonidegib.…”
Section: Safety Tolerability and Adverse Effects Of Sonidegibmentioning
confidence: 99%
“…CK elevation was the most common grade 3/4 event, occurring in 6% of patients taking the 200 mg dose; women show a lower risk of CK abnormality than men 52. Furthermore, CK elevations were observed at low doses in Japanese patients, which resulted in their lower MTD of sonidegib 48,49. Serious adverse events, including rhabdomyolysis and very high CK, were very rarely associated with sonidegib.…”
Section: Safety Tolerability and Adverse Effects Of Sonidegibmentioning
confidence: 99%
“…For example, the SMO inhibitor, vismodegib, was approved by the Food and Drug Administration for the treatment of advanced and metastatic basal cell carcinoma (BCC) ( 33 , 34 ). Vismodegib and numerous other SMO inhibitors, such as sonidegib ( 35 38 ) and saridegib ( 39 , 40 ), are currently undergoing clinical trials in the treatment of BCC and many types of solid tumors ( 25 ).…”
Section: Introductionmentioning
confidence: 99%
“…The safety, efficacy and tolerability of sonidegib have been investigated as monotherapy or in combined therapies in human trials for the clinical management of several advanced solid tumors. For MB patients, the treatment with sonidegib has been reported in four clinical trials Table 1 [31,32]. A phase I trial on patients with recurrent or refractory MB (NCT01125800) showed that oral once daily sonidegib administration (680 mg/m 2 related to the Body Surface Area, BSA) was well tolerated in children and had antitumor activity in both pediatric and adult patients with relapsed SHH-MB (Table I) [31].…”
Section: Sonidegib (Nvp-lde225 Lde-225) Sonidegibmentioning
confidence: 99%
“…Clinical trials are being conducted to evaluate the efficacy of vismodegib and sonidegib in MB. These two drugs are known to be targeting the upstream receptor SMO and have already been approved by the Food and Drug Administration (FDA) for treating metastatic or locally advanced BCC [30][31][32]. However, the responses to SMO inhibitors have been variable, likely due to SMO drug-resistance mutations.…”
Section: Introductionmentioning
confidence: 99%